Genome-wide Mendelian randomization identifies putatively causal gut microbiota for multiple peptic ulcer diseases - Zhao, Jingwei; Hou, Yucheng; Xie, Tianyi; Zhu, Yizhang; Feng, Xinyi; Zhang, Yong; Yang, Ziyi; Gong, Wei (Frontiers in Immunology, 2023)
Objective: The pathogenesis of peptic ulcer diseases (PUDs) involves multiple factors, and the contribution of gut microbiota to this process remains unclear. While previous studies have associated gut microbiota with peptic ulcers, the precise nature of the relationship, whether causal or influenced by biases, requires further elucidation. Design: The largest meta-analysis of genome-wide association studies was conducted by the MiBioGen consortium, which provided the summary statistics of gut microbiota for implementation in the Mendelian randomization (MR) analysis. Summary statistics for five types of PUDs were compiled using the FinnGen Consortium R8 release data. Various statistical techniques, including inverse variance weighting (IVW), MR-Egger, weighted median (WM), weighted mode and simple mode, were employed to assess the causal relationships between gut microbiota and these five PUDs. Result: In the intestinal microbiome of 119 known genera, we found a total of 14 causal associations with various locations of PUDs, and reported the potential pathogenic bacteria of Bilophila et al. Among them, 4 had causal relationships with esophageal ulcer, 1 with gastric ulcer, 3 with gastroduodenal ulcer, 4 with duodenal ulcer and 2 with gastrojejunal ulcer. Conclusion: In this study, the pathogenic bacteria genera in the gut microbiota that promote the occurrence PUDs was found to be causally related. There are multiple correlations between intestinal flora and PUDs, overlapping PUDs have overlapping associated genera. The variance in ulcer-related bacterial genera across different locations underscores the potential influence of anatomical locations and physiological functions.